2011
DOI: 10.1002/chem.201100512
|View full text |Cite
|
Sign up to set email alerts
|

Click Assembly of Dye‐Functionalized Octasilsesquioxanes for Highly Efficient and Photostable Photonic Systems

Abstract: New hybrid organicinorganic dyes based on an azidefunctionalized octasilsesquioxane (POSS) as inorganic part and a 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BDP) chromophore as the organic component have been synthesized by copper(I)-catalyzed 1,3-dipolar cycloaddition of azides to alkynes. We have studied the effect of the linkage group of BDP to the POSS unit and the degree of functionalization of this inorganic core on the optical properties by comparison with model dyes. The high fluorescence ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…[31] Whereas TBTA (Scheme 3), a widely used accelerating copper(I)-ligand, did not have a significant effect on the outcome of diazide reactions, Finn and co-workers have described that some (benz-A C H T U N G T R E N N U N G imidazolylmethyl)amine ligands (e.g., A C H T U N G T R E N N U N G (BimC 4 A) 3 , Scheme 3) gave the monotriazole as the major product in the expected 2:1 mono-/bis-triazole statistical ratio in one example of conformationally rigid 1,3-diazide using a 1:1 diazide/alkyne reaction stoichiometry. [24] Based on the previous statistical calculations, we selected a rather conservative tenfold molar excess of 6 over alkyne 7 a to guarantee a very high statistical selectivity for the monofunctionalized product 7 (Table 1, entry 1). [21] The reaction could be easily followed by TLC by simple naked eye inspection, and affords a POSS derivative 7 (Scheme 1) labeled with a single fluorescent probe and seven additional reactive azide groups ready for further functionalization with any molecule of interest having a terminal alkynyl group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31] Whereas TBTA (Scheme 3), a widely used accelerating copper(I)-ligand, did not have a significant effect on the outcome of diazide reactions, Finn and co-workers have described that some (benz-A C H T U N G T R E N N U N G imidazolylmethyl)amine ligands (e.g., A C H T U N G T R E N N U N G (BimC 4 A) 3 , Scheme 3) gave the monotriazole as the major product in the expected 2:1 mono-/bis-triazole statistical ratio in one example of conformationally rigid 1,3-diazide using a 1:1 diazide/alkyne reaction stoichiometry. [24] Based on the previous statistical calculations, we selected a rather conservative tenfold molar excess of 6 over alkyne 7 a to guarantee a very high statistical selectivity for the monofunctionalized product 7 (Table 1, entry 1). [21] The reaction could be easily followed by TLC by simple naked eye inspection, and affords a POSS derivative 7 (Scheme 1) labeled with a single fluorescent probe and seven additional reactive azide groups ready for further functionalization with any molecule of interest having a terminal alkynyl group.…”
Section: Resultsmentioning
confidence: 99%
“…[41] Both, MR and DC-SIGN bind to glycan patterns present on the surface of pathogens through multivalent carbohydrateprotein interactions. In addition, the covalent attach- ment of the BODIPY chromophore to the inorganic cage of POSS confers an improved photostability to the multivalent construct as we have described recently, [24,43] which is particularly important for the new imaging techniques developed in optical microscopy that require high-laser-intensity irradiation. In addition, the covalent attach- ment of the BODIPY chromophore to the inorganic cage of POSS confers an improved photostability to the multivalent construct as we have described recently, [24,43] which is particularly important for the new imaging techniques developed in optical microscopy that require high-laser-intensity irradiation.…”
Section: And 4 Respectively) the Tetramine [Cu-a C H T U N G T R E mentioning
confidence: 97%
See 1 more Smart Citation
“…Cubic silsesquioxanes constitute a group of organosilicon compounds with the chemical formula (RSiO 3/2 ) 8 (where R is H, alkyl, aryl, etc.). [15][16][17][18] Phthalimide and o-sulfobenzimide-functionalized silsesquioxanes have been found to be promising materials for the further functionalization of other nitrogen-based POSS. Covalently bonded organic arms make reactive functionalities suitable for polymerization or grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Optical, light scattering and scanning electron microscopy (SEM) investigations on POSS@TPPS adduct demonstrated that the ''bulky'' POSSNMe 3 + acts as a highly dispersing agent toward the TPPS tetraanion, reducing its well known aggregation tendency, both in solution and in the solid state [17]. Hence, ionic self-assembly promoted by amphiphilic POSS-ILs turned out to be a useful alternative strategy to access, with respect to conventional covalent approaches [19][20][21], to novel POSS-multifunctional materials.…”
Section: Introductionmentioning
confidence: 99%